Collecting Phaseolus in Costa Rica - Debouck, Daniel G.; Araya Villalobos, Rodolfo; Ocampo S., R.A.; González Ugalde, W.G. (1989)
A survey was carried out in Central Costa Rica in Jan. 1987, in an attempt to find web blight resistance in native var.; 43 samples representing 10 different taxa were found. Wild P. vulgaris was found in 2 different places in the province of San Jose; both populations presented truly wild characteristics as to growth habit (climbing vines on thickets, 2-3 m high) and seed characteristics (small, flat, roundish, shiny, grey-mottled, and 100-seed wt. of 4.9 g). A species called P. costaricensis was also found; in all populations, it presented strong climbing stems up to 10 m high, strong large, upright and multiflowered racemes, brilliant pink fuschia flowers with a capitate extorse stigma, and epigeal germination. Another species was apparently new: purplish flowers, large stipules, and large ovate, early caducous primary bracts. The name of P. talamancensis has been proposed. Symptoms of web blight were not observed in many of these wild populations (P. tuerckheimii and P. xanthotrichus), but these results are not conclusive since several of these populations were found outside the endemic areas. Further phytopathological assessments are required. (CIAT)